2013
DOI: 10.3892/mmr.2013.1836
|View full text |Cite
|
Sign up to set email alerts
|

Fisetin inhibits migration, invasion and epithelial-mesenchymal transition of LMP1-positive nasopharyngeal carcinoma cells

Abstract: Fisetin (3,3',4',7-tetrahydroxyflavone) has been reported to possess certain anticancer properties. It may inhibit tumor cell proliferation, metastasis and induce apoptosis. However, the effects of fisetin in preventing the metastasis of nasopharyngeal carcinoma (NPC) cells remain to be determined. The epithelial-mesenchymal transition (EMT) is involved in several metastatic malignancies including NPC. It has been reported that the Epstein-Barr virus latent membrane protein-1 (LMP1) induced EMT and is associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 22 publications
4
15
0
Order By: Relevance
“…The investigation demonstrated that fisetin suppressed the migration and invasion of CNE1-LMP1 cells under non-cytotoxic concentrations. Fisetin up-regulated the epithelial marker, E-cadherin and down-regulated the mesenchymal marker, vimentin accompanied by significant reduction in the levels of the EMT regulator Twist protein [64]. …”
Section: Anti-cancer Activity Of Fisetinmentioning
confidence: 99%
“…The investigation demonstrated that fisetin suppressed the migration and invasion of CNE1-LMP1 cells under non-cytotoxic concentrations. Fisetin up-regulated the epithelial marker, E-cadherin and down-regulated the mesenchymal marker, vimentin accompanied by significant reduction in the levels of the EMT regulator Twist protein [64]. …”
Section: Anti-cancer Activity Of Fisetinmentioning
confidence: 99%
“…Previously, fisetin has shown anti-proliferative, anticancer, neuroprotective, and antioxidant activities [1012]. In recent years, Fisetin has been reported to inhibit cell proliferation, migration and invasion, and induce apoptosis in several cancer types, such as colon cancer [13], glioma cancer [14], lung cancer [15], nasopharyngeal carcinoma [16], prostate cancer [17], and bladder cancer [18] and cervical carcinoma[19]. It also inhibits micro-ophthalmia associated transcription factor (MITF) in melanoma cells and inhibits invasion of melanoma cells via modulation of the MAPK and NF-κB pathways [20–22].…”
Section: Introductionmentioning
confidence: 99%
“…Only one published research article has focused on the potential targeting of oncoviruses and EMT in NPC (116). Fisetin is a flavonol, a structurally distinct chemical substance that belongs to the flavonoid group of polyphenols, and it has been reported as having certain anticancer properties.…”
Section: Clinical Application and Anti-emt Targeted Therapymentioning
confidence: 99%